2012
DOI: 10.1002/ccd.24476
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of safety, accuracy, and human CD34+ cell retention after intramyocardial injections with a helical needle catheter in a porcine model

Abstract: Helix system was accurate and safe. Retention of CD34+ cells was confirmed by MRI and immunohistology. Further preclinical studies are needed to characterize retention over time and quantify efficiency. Studies are needed to confirm accuracy, safety, and retention in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Among them, the number of injections may be an important factor as more injections may cause potential myocardial damage, through multiple mechanisms both mechanical and biological (such as inflammation). Indeed, a U‐shaped dose–response relationship has recently been proposed in other stem cell therapy studies, with maximal efficacy achieved with a lower number of injections . This inverse dose response to MSC therapy in reducing LV volumes has been documented in the setting of clinical ischaemic cardiomyopathy, supporting the concept that excessive therapeutic intensity may offset benefit …”
Section: Introductionmentioning
confidence: 85%
“…Among them, the number of injections may be an important factor as more injections may cause potential myocardial damage, through multiple mechanisms both mechanical and biological (such as inflammation). Indeed, a U‐shaped dose–response relationship has recently been proposed in other stem cell therapy studies, with maximal efficacy achieved with a lower number of injections . This inverse dose response to MSC therapy in reducing LV volumes has been documented in the setting of clinical ischaemic cardiomyopathy, supporting the concept that excessive therapeutic intensity may offset benefit …”
Section: Introductionmentioning
confidence: 85%
“…Stem cells (or saline solution controls) were delivered intramyocardially to 8 infarct and peri‐infarct zones using the Helix Helical Infusion System, a distal helical needle, and a Morph Universal Deflectable Guide Catheter (BioCardia Inc). Validated protocols for this fluoroscopically guided cell delivery system in large animals and humans have been described (Figure ). Briefly, the targeted region was defined by MEMRI and delayed gadolinium enhancement magnetic resonance imaging (DEMRI), and then right and left anterior‐oblique ventriculograms were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Manual tracings documenting the locations of the injections are shown from (C and D) 2 different fluoroscopic projections. The sternum is used as an anatomical landmark, and the locations of injection are tracked numerically as marked …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Kumar, et al have demonstrated percutaneous TE cell delivery using this system under only fluoroscopic guidance to be accurate and safe. 30) This is the first study to evaluate stem cell delivery efficacy using the Helix transendocardial delivery system compared with other frequently used delivery methods of IC infusion and direct TP injection. In this study, significantly more cells were retained after TE injection than either TP injection with a straight needle or IC infusion.…”
Section: Discussionmentioning
confidence: 99%